Pengaruh Motivasi, Komitmen dan Lingkungan Kerja Bagi Kinerja Perawat RSU Rajawali Citra - Verliana Setyaningrum; Dila Damayanti (STIE Wiyatamandala, 2023)
The purpose of this study was to determine the effect of the work environment, work commitment and motivation on employee performance, especially nurses at RSU Rajawali Citra, Bantul Regency. The analytical method used by the authors in conducting this research is to use quantitative research with a population of 65respondents who are nurses in RSU Rajawali. In this study the variables were divided into several parts including motivation (X1), work commitment (X2) and work environment (X3) as independent variables, and employee performance (Y) as the dependent variable. The results of this study indicate that motivation has asignificant effect on the performance of nurses at RSU Rajawali Citra, while work commitment and work environment have no effect on the performance of nurses at RSU Rajawali Citra.